If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7y + 33) = (3y + -3) Reorder the terms: (33 + 7y) = (3y + -3) Remove parenthesis around (33 + 7y) 33 + 7y = (3y + -3) Reorder the terms: 33 + 7y = (-3 + 3y) Remove parenthesis around (-3 + 3y) 33 + 7y = -3 + 3y Solving 33 + 7y = -3 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 33 + 7y + -3y = -3 + 3y + -3y Combine like terms: 7y + -3y = 4y 33 + 4y = -3 + 3y + -3y Combine like terms: 3y + -3y = 0 33 + 4y = -3 + 0 33 + 4y = -3 Add '-33' to each side of the equation. 33 + -33 + 4y = -3 + -33 Combine like terms: 33 + -33 = 0 0 + 4y = -3 + -33 4y = -3 + -33 Combine like terms: -3 + -33 = -36 4y = -36 Divide each side by '4'. y = -9 Simplifying y = -9
| (t^2+4t-1)(2t^2-t-3)= | | 8z-7=3z-2 | | 4=2w+1 | | 2(x+11)=104 | | 0,02=2/100 | | X(.45)=x-66 | | x-12+49+90=180 | | x^2+16x=4x-35 | | 5x+13=5x-2 | | 14n-2-7n=37 | | 9x=100-19 | | 2h=6-4h | | 4(k-8)-8=-46+4k | | -0.375r-11=4 | | -28x-21=7x^2 | | 3(r+4)=9 | | 50p-26=51p-68 | | Y-(-5)=0.5(x-(-8)) | | -10=14x+14x | | (3x-4)(2x^2+3x+3)= | | 6x^2=4x+7 | | -7w+2(w+6)=9-(4w-10) | | 5*10.2-8=43 | | 4(5y-3.8)+14.8=2(7y-0.2) | | x^2+5ax+6a^2=0 | | 8(8-x)=4(x+10) | | 6w-15=8w | | 5y-55=4x+5 | | X^2-2x+3x-27=105 | | Y-(-3)=-4(x-1) | | 2x-7+2x-5+x-1=(3x-11)2+2(x-3) | | -2x+20=14 |